Social software supported children's education out of school: informality and transition of learning - Yang, Yang (2011)
This thesis is motivated to harness UK children’s enthusiasm and energy on using social software to connect with each other. The overarching research aim of this thesis is to investigate how social software can cultivate children aged 11 – 14 as a community of learners out of school, in order to support their education. Two key issues: informality of out-of-school learning and transitions of learning practices across home and school, are identified as research challenges. Community of Practice is proposed as the theoretical construct to open up and provide useful coverage to respond to these two challenges. In five case studies, various methodologies are utilised to investigate the actual uses that children make of social software as well as to explore the networked dynamics within a community that mediate the fate of technology.